Menganalisis Surat Al-Alaq Ayat 1-5 Tentang Belajar Berdasarkan Tafsir Tarbawi - Tiara Anggraini; Della Marsya Pratama (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to explore the learning found in Surah al-'Alaq Verses 1–5 of the Koran, as they include a plethora of information regarding the significance of learning. There are also other verses in the Qur'an that explain the principles of learning in the sense of researching and gaining knowledge for the benefit and supremacy of humanity.The principal source of information used by the author is the Koran, along with verses 1–5 of surah al-'Alaq and other sections that discuss learning and its interpretation.